Perceived stress among newcomer students in Gandaki Medical College: A cross-sectional study - Thapa, Bindu; Silwal, Muna; Gurung, Sunita; Koirala, Dipti; Katel, Kalpana (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Medical students perceive medical education as stressful, which has both positive and negative effects on physical and psychological health. The mental health of a medical student remains affected throughout training due to long study and working hours, extensive course content, examinations, peer competition, uninspiring environments, sleep deprivation, and loneliness. Hence, the objective of this research was to assess the prevalence of stress among newcomer students at Gandaki Medical College.Methods: A descriptive cross-sectional study was conducted among 195 newcomer students at Gandaki Medical College in Kaski, District. Data was collected on orientation dated May 21,2021 at the GMC. A complete enumerative technique was used. Data was collected using the self-administered Perceived Stress Scale (PSS-10) tool. Descriptive (mean, frequency, percentage, and standard deviation) and inferential (chi-square test) statistics were applied for data analysis in Statistical Package for Social Science (SPSS) version-16.0.Results: Most of the respondents 163(83.58%) reported moderate stress, 18(9.23%) reported high stress and 14(7.19%) reported low stress. Stress among students was found to be significantly associated with residence (p=0.02) and type of family(p=0.04).Conclusions: Most respondents reported moderate stress. The research findings highlight counselling is an integral part of newcomer students to prevent stress.